MUSICAL EDUCATION VERSUS MAN OF CONTEMPORARY SOCIETY - Stela GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
The achievements and use of the new technologies provide contemporary education with a new structure of the social requirements. Owing to the social progress, education has become much more active, an operating factor of progress, preparing people according to the requirements of the future society. Music education prepares the individuals to understand and adequately adapt to the contemporary social culture and, through specific actions, it ensures the formation and development of their cultural creativity. Along with the other forms of art, music contributes to the society’s cultural continuity and stability. In addition, it gives birth to a vigorous dynamic interaction between the members of a group sharing the same national, religious, cultural or ideological identities. Music plays an important part in contemporary education, as part of the human culture, as a powerful means of emotional expression and interpersonal communication, as an expression of national, religious and cultural identity, as well as a means of contact, communication and exchange between different cultures, nations and religions, as a means of recreation, entertainment and aesthetic enjoyment.